Center stage - Nathan, Sarah (Shake it up, 2012)
CeCe Jones and Rocky Blue, best friends and enthusiastic dancers, audition as background dancers for the hit television show, "Shake It Up, Chicago" but, when CeCe freezes during her tryout, they fear they may not be able to perform together.